Associação da hidroxiapatita e beta-tricálcio fosfato incorporados em culturas de células-tronco, obtidas de dentes decíduos esfoliados humanos, em defeitos de calvária de ratos - Silva, Alexandre Augusto Ferreira Da (2021)
Several studies have investigated the effect of biomaterials in filling bone defects. The higher postoperative morbidity associated with donor area restrictions for autogenous bone grafts and the greater demand for less invasive surgical procedures have brought different biomaterials with different compositions to the bone grafting market. Bioceramics based on biphasic calcium phosphate (BCP) composed of hydroxyapatite (HA) associated with beta-tricalcium phosphate (β-TCP) have been an alternative to the autogenous bone graft with characteristics related to the bone components. This in vivo study investigated the effect of the incorporation of stem cells originated from the pulp of human exfoliated deciduous teeth (SHED), into the granules of BCP when used as a filling material in calvarial defects in metabolically normal adult rats. A critical size defect measuring 6 mm in diameter, per animal, was performed in the calvarial of 50 rats. BCP granules with 60% HA and 40% β- TCP with an average size of 250 to 420 μm were used and incorporated into SHED cultured for 7 days in conventional culture medium (MC) or osteogenic culture medium (MO). The animals were divided into 5 groups with 10 animals each: clot (CO), autogenous bone (AUT), BCP, BCP + SHED in MC (BCP-MC) and BCP + SHED in MO (BCP-MO). Euthanasia occurred after 4 and 8 weeks. Bone neoformation and presence of biomaterial residual particles were assessed using histometry and the chronic inflammatory process through qualitative histological analysis. The lowest bone neoformation was observed in the CO group for 4 and 8 weeks with no significant difference between the periods (p = 0.9999). The AUT group had the highest average in bone neoformation and was statistically different (p <0.05) from all other groups after 8 weeks and when the entire study period was evaluated. After 8 weeks, the BCP-MC and BCP-MO groups showed homogeneity in bone neoformation (p = 0.1363). Throughout the study period, the BCP group had the highest percentage of residual biomaterial particles, however, it was statistically equal to the BCP-MC group (p = 0.0604) and different (p = 0.0104) from the BCP-MO group. The BCP-MC and BCP-MO groups were the same (p = 0.5920) in terms of the presence of biomaterial residual particles. The chronic inflammatory infiltrate was considered mild at 4 and 8 weeks in a xenogenous SHED transplant for rats without immunodeficiency. Thus, considering the limitations of this study, we concluded that BCP particles incorporated with SHED in MC or MO showed homogeneous results, however, inferior to the autogenous bone graft for filling critical calvarial defects in rats.